Commodity market review: 1996 - 1997 - FAO (FAO, 1997)
This is the second issue of the annual Commodity Market Review ( CMR ), which replaced the Commodity Review and Outlook, the previous FAO publicaton on commodities and trade. At the first issue, this review is presented in two sections. Part 1 provides a synthesis of key developments in the global economy, commodity prices and export earnings as well as other developments affecting international trade in agriculture. It also summarizes selected recent FAO studies on commodities and trade issues as well as the activities of the FAO Intergovernmental Commodities Bodies. Part 2 reviews the current world market situation for 21 individual commodities in agriculture, fishery and forestry and discusses the short-term outlook. These individual notes focus on market developments and complement the more detailed commodity information and analysis available from FAO. This Review also lists the names and addresses of individual commodity specialists who may be contated for further information.